Capital investments as an object of financial controlling - S.M. Ratushnyi (Економіка, управління та адміністрування, 2024)
The article is devoted to capital investments as an object of financial controlling. The purpose of the article is to evaluate theoretical approaches to the determination of capital investments, to analyze the dynamics of capital investment indicators in the country as a prerequisite for identifying the influence of external and internal environmental factors on the investment activity of enterprises, and to justify the need to implement financial controlling tools by business entities. It was determined that consideration of capital investments as an object of financial controlling is considered fragmentary by modern scientists, while the study of investments within the framework of controlling the entire investment activity of enterprises is quite common. Specific features of capital investment as an object of financial controlling are singled out, namely: 1) capital investment is the investment of capital with a predetermined goal - its increase; 2) capital investment is a long-term investment of capital; 3) capital investments have different forms, types and sources of financing; 4) making effective capital investments at the enterprise is a sign of its long-term financial stability; 5) the adequacy and effectiveness of capital investments determines the investment activity of individual enterprises and the state. It is substantiated that the significance of the study of capital investments as an object of financial controlling is due to their importance for ensuring the long-term financial stability of business entities (at the micro level) and ensuring the normal reproductive process of the country's fixed capital (at the macro level). At the same time, the development of market relations determines the transformation of scientific approaches to the essence, forms, methods and principles of capital investments, which determines the need for innovative management technologies, which is the financial controlling system. The conducted financial analysis based on a set of indicators (amounts of capital investments in tangible assets by their types; main types of economic activity, indices of capital investments by types of activity, the impact of the amount of capital investments on the volume of GDP) made it possible to reveal the influence of external factors (political, economic, social, scientific and technological) and internal (production-technical, financial, organizational-management) environment on the investment activity of business entities. Awareness of the negative impact of external and internal environmental factors on the investment activity of enterprises in recent years requires the search for new adaptive management technologies aimed at restoring the level of investment activity, including with the help of the tools of the financial controlling system. Prospects for further scientific research should be linked to the modelling of the system of financial controlling of capital investments at enterprises.